Bribery and corruption : navigating the global risks - Loughman, Brian P.; Sibery, Richard A. (Hoboken, N.J. : John Wiley & Sons, 2012)
'A practical guide to understanding and counteracting accounting fraud around the world. As businesses continue to expand globally into new and emerging markets, bribery and corruption risks have increased exponentially. The Accountant's Guide to Bribery and Corruption Risks offers a comprehensive look at this growing problem, and at the Foreign Corrupt Practices Act (FCPA) and other international anti-bribery and corruption conventions. Presenting hypothetical examples of situations companies will face, along with practical solutions, the book offers detailed global guidance on a region and country-specific basis.The FCPA prohibits US companies and their subsidiaries from bribing foreign officials, either directly or indirectly through intermediaries, for the purpose of obtaining or retaining business. It also requires companies to keep accurate records of all business transactions and maintain an effective system of internal accounting controls. Internationally, the Organization of Economic Cooperation and Development's (OECD's) anti-bribery convention has been adopted by 38 countries and creates legally binding standards related to bribery of foreign public officials.Written by renowned accounting fraud experts Jeffrey Taylor, Richard A. Sibery, and Brian P. Loughman, and providing an introduction and overview of the Foreign Corrupt Practices Act (FCPA) and international bribery laws, The Accountant's Guide considers: How to conduct FCPA risk assessments and investigations How to consider FCPA specific financial controls How to implement an FCPA compliance program and how to measure FCPA compliance The risk of bribery and corruption continues to be an area of concern for companies around the world, but armed with The Accountant's Guide to Bribery and Corruption Risks, it is easier than ever to understand the challenges that exist and how to deal with them'--
Published simultaneously in Canada.
Includes bibliographical references and index.
Keywords: International business enterprises -- Law and legislation -- Criminal provisions; Bribery; Corporations, Foreign -- Corrupt practice